Renewable Energy Education through Solar-Powered Toy Car Assembly Activities for Junior High School Students - Tri Arif Wiharso; Helfy Susilawati; Akhmad Fauzi Ikhsan; Gandi Sugandi; Putri Asti Meilani; Agistian Hendryansyah; Dama Robiul Awaludin (Jurnal IPTEK Bagi Masyarakat, 2026)
Renewable energy sources are a solution to fossil energy sources, which are increasingly depleting every day. Renewable energy has various types; however, the most widely used at present is solar energy, commonly referred to as solar power generation (photovoltaic systems). The development of solar power in Indonesia has begun to be implemented in several sectors to support government programs, particularly national energy security. Considering the importance of renewable energy, early socialization and education are needed, especially for junior high school students. Early education is expected to raise students’ awareness of the importance of environmental preservation in maintaining renewable energy resources provided by nature. To make the educational process more engaging, a hands-on practice method was applied. In this community service activity, students assembled solar-powered toy cars so that the cars could operate. This activity aimed to directly involve students in the use of renewable energy and to help them understand how renewable energy can be applied in simple applications. The results show that students were able to complete the assembly of solar-powered toy cars; 48.28% of students rated the activity as very beneficial, 48.28% as beneficial, and 3.45% as moderately beneficial. Based on these results, it can be concluded that the community service activity was successfully implemented.